2014
DOI: 10.1016/j.ridd.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Visuo-spatial ability in individuals with Down syndrome: Is it really a strength?

Abstract: Down syndrome (DS) is associated with extreme difficulty in verbal skills and relatively better visuo-spatial skills. Indeed, visuo-spatial ability is often considered a strength in DS. However, it is not clear whether this strength is only relative to the poor verbal skills, or, more impressively, relative to cognitive ability in general. To answer this question, we conducted an extensive literature review of studies on visuo-spatial abilities in people with Down syndrome from January 1987 to May 2013. Based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
61
1
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 126 publications
(195 reference statements)
7
61
1
7
Order By: Relevance
“…Pursuing this line of reasoning, a review of four studies on wayfinding with individuals who have Down syndrome in fact suggests limitations in wayfinding abilities, although the authors express concern about factors related to the internal validity of the small number of studies and call for more research [59]. Other research points to a reliance on route rather than configurational knowledge in Down syndrome individuals [60].…”
Section: Wayfindingmentioning
confidence: 99%
“…Pursuing this line of reasoning, a review of four studies on wayfinding with individuals who have Down syndrome in fact suggests limitations in wayfinding abilities, although the authors express concern about factors related to the internal validity of the small number of studies and call for more research [59]. Other research points to a reliance on route rather than configurational knowledge in Down syndrome individuals [60].…”
Section: Wayfindingmentioning
confidence: 99%
“…Yang et al . () have noted, however, that our knowledge of the visuospatial skills of individuals with DS is limited by the fact that most studies have investigated small‐scale abilities, that is, those measured using pencil‐and‐paper tasks. Few studies have examined large‐scale abilities, for example, moving in a virtual environment and remembering its features (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to represent an environment is primarily tied to visuospatial abilities, which are believed to represent a relative strength within the cognitive profile of DS (Davis, 2008;Silverman, 2007). However, this 'strength' has been questioned, as it may depend on which specific aspects of visuospatial ability are considered (Yang, Conners, & Merrill, 2014). For example, individuals with DS are not better at tasks requiring mental rotation than typically developing (TD) individuals of the same mental age (Hinnell & Virji-Babul, 2004;Vicari, Bellucci, & Carlesimo, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated that DS is characterized by relatively preserved visuospatial abilities but impaired language skills (Moldabsky, Lev, & Lerman-Sagie, 2001; but see Yang, Conners, & Merrill, 2014). One would expect that this relative visuospatial ability would predict relative ability in comparing both area and numerosity.…”
mentioning
confidence: 96%